Antisite disorder mediated exchange bias effect and spin-glass state in La2−xSmxNiMnO6 - Hissariya R.; Sathe V.G.; Mishra S.K. (My University, 2025)
We report the synthesis of La2−xSmxNiMnO6 (x = 0, 0.1, 0.2) polycrystalline compounds through the sol–gel process using all-aqueous precursors. The influence of Sm-substitution on magnetic properties of La2−xSmxNiMnO6 (LSNMO) compounds are investigated through X-ray diffraction (XRD), dc-magnetization (Mdc), ac-magnetic susceptibility measurements, and Raman spectroscopy. XRD analysis confirms that the phase stability of LSNMO is improved significantly upon Sm-substitution as evident from a structural phase transformation of the compound from a biphasic (monoclinic + rhombohedral) into an aphasic (monoclinic) structure. The magnetic measurements indicate a formation of a metastable magnetic state with random ferromagnetic (FM) and antiferromagnetic (AFM) interactions below 100 K. The metastable spin configuration exhibits critical slow-down dynamics and memory effect that signifies a spin-glass (SG) state. The influence of Sm-doping reduces the Curie temperature (Tc) from 284 K → 245 K and enhances saturation magnetization (Ms). These findings are attributed to the combined effect of a reduced degree of antisite disorder upon the addition of Sm. A profound variation (45.5 → 72.9 K) in SG transition temperature (TSG) is also reported. Magnetization loops M(H) confirm the presence of an exchange bias (EB) effect that value suppressed prominently from 120 → 28 Oe upon Sm-substitution. The temperature-dependent magnetization M(T) and frequency-dependent ac-susceptibility χ[ω, T] are used to study the antisite-driven SG phase, spin relaxation dynamics, magnetic memory, and rejuvenation effect. Raman spectroscopy is employed to probe the degree of antisites disorder that reduces after Sm-addition. The phase stability, lower Tc, tunable Ms, and EB in the single-phase compound make LSNMO a potential candidate for its applications in realizing energy-efficient devices. © 2023 Elsevier B.V.